Evaluasi Kinerja Internal PT.Kimia Farma untuk Menjaga Keterampilan dan Motivasi Sumber Daya Manusia - Dwiki Cahyo Yudiantoro; Bambang Soedijono WA; Ferry Wahyu Wibowo (Journal of Information Technology, 2021)
In the modern era, an internal control system cannot be separated from the development of information technology. When a company's business grows and the need for information increases, usually the company will improve its information technology system and technology is one of the top priorities in internal control in an organization or company. The development of information technology is currently very fast and provides positive benefits for the company. The role of information technology is needed for company progress in the process of business development and obtaining information that is fast, accurate, and reliable. To find out the alignment of information technology and maintain employee performance motivation and the role of technology itself, an audit of a company or organization is necessary. This is done in order to get good decision results based on the results of the audit within the organization or company. The research object that the authors take here is PT. Kimia Farma in 2019 using the COBIT 4.1 Framework and with the data collection method using interviews and questionnaires distributed to related parties. The results of this study were to determine maintaining the value of skills and motivation of human resources at PT. Kimia Farma and it is hoped that the quality and human resources will continue to be maintained and improve.